2010
DOI: 10.1016/j.hlc.2010.06.727
|View full text |Cite
|
Sign up to set email alerts
|

Framingham Risk Prediction Equations for Incidence of Cardiovascular Disease Using Detailed Measures for Smoking

Abstract: Current prediction models for risk of cardiovascular disease (CVD) incidence incorporate smoking as a dichotomous yes/no measure. However, the risk of CVD associated with smoking also varies with the intensity and duration of smoking and there is a strong association between time since quitting and the risk of disease onset. This study aims to develop improved risk prediction equations for CVD incidence incorporating intensity and duration of smoking and time since quitting.The risk of developing a first CVD e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Individuals were considered smokers if they reported that they were currently smoking or when they had stopped smoking less than 5 years ago …”
Section: Methodsmentioning
confidence: 99%
“…Individuals were considered smokers if they reported that they were currently smoking or when they had stopped smoking less than 5 years ago …”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria were missing informed consent, severe renal failure defined as estimated glomerular filtration rate (GFR) ≤ 30 ml/min according to the MDRD formula [25], severe liver dysfunction (defined as chronic hepatic disease, e.g., cirrhosis, or previously documented biochemical evidence of significant hepatic derangement) [26], and atherothrombotic events -namely acute coronary syndromes, stroke, transient ischemic attack or any cardiovascular intervention within 4 weeks prior to study enrollment. Additional exclusion criteria for the control group were excessive smoking history (N 10 pack-years) [27], diabetes mellitus (fasting plasma glucose ≥ 7 mmol/l, or hemoglobin A1 c ≥ 6.5%), hypertension (ambulatory blood pressure N 140/90 mm Hg, or antihypertensive medication), hyperlipidemia (LDL-cholesterol ≥ 4.1 mmol/l) or history of venous thromboembolism.…”
Section: Subjectsmentioning
confidence: 99%
“…This equation considers gender, age, systolic blood pressure, smoking status, total cholesterol, HDL-C, and diabetes mellitus status to calculate the percentage likelihood of a coronary disease over a 10year period [37].…”
Section: Novel Cardiovascular Risk Scoresmentioning
confidence: 99%